HUBUNGAN ANTARA DURASI BERMAIN GAME PADA GADGET TERHADAP PRESTASI AKADEMIK SISWA KELAS V DAN VI SDIT AL ISTIQOMAH PRABUMULIH - Dluhrohning Sundari; Wakib Kurniawan (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to determine the relationship between the duration of playing games on gadgets and the academic achievement of fifth- and sixth-grade students at SDIT Al Istiqomah Prabumulih. The method used in this research was a quantitative correlational study with data collection techniques in the form of questionnaires and report card score documentation. The research sample consisted of 117 students. Data analysis was conducted using the Pearson Product Moment Correlation test. The results showed a correlation coefficient of r = -0.249 with a p-value of 0.007 (< 0.05), indicating a significant negative relationship between the duration of playing games on gadgets and students’ academic achievement. The higher the duration of playing games, the lower the students’ average report card scores. The coefficient of determination of 6.22% indicates that the duration of playing games contributes 6.22% to students’ academic achievement.